Lack of CD34 positive stromal cells within angiomyomas (vascular leiomyomas). Issue 5 (1st May 2002) - Nakayama, H; Enzan, H; Miyazaki, E; Kuroda, N; Toi, M
Abstract : Aims: To investigate the role of CD34 positive stromal cells in the morphogenesis and tumour growth regulation of angiomyomas (vascular leiomyomas). Methods: Histochemical analysis using monoclonal antibodies to CD34 and CD31 was performed in 10 angiomyomas and their adjacent soft tissue. Results: CD34 positive stromal cells were not seen within the tumour tissue; the thick walled vessels within the tumours lacked CD34 positive stromal cells. In contrast, bundles of CD34 positive stromal cells were detected at the tumour border of all of the angiomyomas and in the adventitial tissue of the surrounding normal vessels. Conclusions: The lack of CD34 positive stromal cells within an angiomyoma is associated with the characteristic morphology of an angiomyoma.